Effects of n-heptane enrichment on in-cylinder thermochemical fuel reforming (TFR) characteristics and performances of spark ignition natural gas engine: A comparison with natural gas and methanol enrichment. (1st July 2020) - He, Zhuoyao; Wang, Jianping; Li, Bolun; Zhu, Lei; Qian, Yong; Lu, Xingcai; Huang, Zhen
Abstract: In this study, the effects of n-heptane enrichment on in-cylinder thermochemical fuel reforming (TFR) characteristics and performances of a spark ignition (SI) natural gas (NG) engine were examined. Methanol and NG enrichment cases were also involved for comparative analyses. It was found that n-heptane enrichment substantially improved NG in-cylinder thermochemical fuel reforming as methanol enrichment did. Under n-heptane enrichment case, H2 and CO in the reformate could reach up to 4%(v) and 6.5%(v), respectively, when equivalence ratio of TFR cylinder reaches 1.40. At the same time, very slight fraction of unburnt hydrocarbon exists in the reformate, indicating a robust fuel reforming in TFR cylinder. With n-heptane enrichment, more stable TFR cylinder combustion was achieved compared with NG enrichment with a concentrated CA50-IMEP distribution for TFR cylinder and lowered standard deviation of IMEP for cylinder #2 (typical of normal cylinders). Besides, compared with NG enrichment, a significantly weaker discrepancy between TFR cylinder and cylinder #2 was achieved with n-heptane enrichment. Similar to methanol enrichment case, n-heptane enrichment did not obviously affect engine CO and THC emissions while remarkably reduced engine NOx emission. With n-heptane enrichment, more than 10 g/kWh BSFC discount could be achieved, though slight knock happens, relative to either NG or methanol enrichment case, indicating better fuel economy.